Pre-clinical development of a vaccine for human lymphatic filariasis - Melendez, Valeria; Turner, Cheri; Khatri, Vishal; Davis, Jenn; Chauhan, Nikhil; Nagalati Sudhakar, Divya Sree; Cabullos, Richard; Carter, Darrick; Gray, Sean A.; Kalyanasundaram, Ramaswamy (Frontiers in Tropical Diseases, 2022)
This study was conducted to optimize a fusion protein vaccine for translational development as a vaccine against the human tropical parasitic infection, lymphatic filariasis (LF). The vaccine candidate, His-tagged rBmHAXT was developed previously in our laboratory and was tested in various animal models including mouse, gerbils and Rhesus macaque where it exhibited significant levels of vaccine-induced protection. However, for commercial manufacturing and for regulatory approval for human use, there was a need to modify the vaccine antigen and its production and analytical release methods. Therefore, the major focus of this study was to develop a process for manufacturing an affinity tag-free rBmHAXT and evaluate its immunogenicity, potency and protective efficacy in both inbred and outbred mouse models, as well as in outbred gerbil models. Our results demonstrate that the tag-free rBmHAXT vaccine produced with a process suitable for cGMP production had protective properties equivalent to the original His-tagged rBmHAXT.